BEBERAPA PELANGGARAN PRINSIP KERJA SAMA SEBAGAI PENYEBAB TERJADINYA EFEK HUMOR PADA WACANA HUMOR POLISI DAN TENTARA E. Zaenal Arifin - E Zaenal Arifin (Universitas Nasional, 2016)
ABSTRACTThis study uses descriptive qualitative method. The data are taken from the book Wacana Humor Polisi danTentara. The population of this study is 37 discourses, the sample selected by a random sampling of 25% as much as10 discourses. The theory to analyze data is Grice Cooperative Principle plus Pragmatics Theory Keywords: thimbles, violation, cooperation, maxim of quality, quantity, relevance.politeness,